Analysis of Multi-Dimensional Layers in Historic Districts Based on Theory of the Historic Urban Landscape: Taking Shenyang Fangcheng as an Example - Yuan Wang; Chengxie Jin; Danyang Xu; Tiebo Wang; Baoxi Wang (Land)
The accelerated process of urbanisation in China is resulting in a decline in and threat to the historic landscape of historic districts. This study is based on the theory of historic urban landscapes and employs a multi-dimensional layers research framework for historic districts. It adopts a single case study and a research method that combines quantitative and qualitative methods. The stratification elements of Fangcheng in Shenyang are identified and summarised, the process of stratification is analysed, and the stratification patterns and laws are summarised through the acquisition and collection of multivariate data. The findings of this study indicate that the stratification elements of the Fangcheng Historic District have undergone five distinct phases of stratification evolution. The resulting stratification pattern can be summarised as follows: newborn, preserve, override, juxtaposition and decession. The spatial elements are layered in the following pattern: The historic landscape can be conceptualised as comprising four layers: (1) the layering of the historic landscape with large public buildings as the anchor point; (2) the layering of the historic landscape with the spatial pattern as the skeleton; (3) the layering of the historic landscape with the iconic buildings as the nodes; and (4) the layering of the historic landscape with the correlative elements as the substrate. The law of value element layering primarily reflects the principles of concentration, diversity and adaptation. In light of the urban historic landscape theory, the reconstruction and restoration strategies, integration of old and new and adaptive conservation of historic landscapes are proposed to offer novel insights and guidance for the conservation of the historic landscape in the Fangcheng Historic District.